Economic System of the European Union. Between Particularism and Universalism - Kubin, Tomasz (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Though the concept of economic system is usually described and analysed in relation to the state, it seems that because of the level of integration and a number of exceptional features, it is worthwhile trying to analyse it with regard to the European Union. Therefore, the paper contains a description and a brief analysis of the European Union as an economic system. The main axis of considerations is the simultaneous occurrence in the system of the particular features peculiar to the individual EU member states, and the universalistic ones, resulting from the integration process. The first part of the article indicates specific features of the EU as an economic system. This is useful and necessary in order to understand the uniqueness of the EU as an economic system. The second part of the article concerns the theoretical aspects of the EU as an economic system. Subsequently, the selected aspects how the EU works in practice as an economic system are contained in the third part. To this aim, statistical data relating to about ten different criteria have been used. The summary and the main conclusions are at the end of the article. Key words: economic system, the European Union